Approaches, applications, and future directions for hyperspectral vegetation studies: An emphasis on yield‐limiting factors in wheat. Issue 1 (19th May 2020) - Bruning, Brooke; Berger, Bettina; Lewis, Megan; Liu, Huajian; Garnett, Trevor
Abstract: Hyperspectral instruments acquire spectral information in many narrow, contiguous bands throughout the visible, near‐infrared and shortwave regions of the electromagnetic spectrum. Hyperspectral techniques are becoming very powerful tools for characterizing plants and nondestructively quantifying their chemical and physical properties because of their ability to provide layered trait information within the same spectral region. However, to effectively make use of hyperspectral sensing, an understanding of the theory behind these techniques, the power, and the limitations of the resulting data is required. This article presents an overview of hyperspectral sensing in regard to principles, instrumentation, processing methods, and current applications, specifically focusing on the quantification of yield‐limiting factors in wheat ( Triticum aestivum L.). The spectral properties of plants across the electromagnetic spectrum are first described to achieve a better understanding of plant–light interactions. Basic information about different imaging approaches is provided as are the necessary considerations for the analysis of hyperspectral data. Some of the major technical challenges associated with hyperspectral imaging as well as future directions are discussed. Finally, as an example crop, the use of hyperspectral techniques for quantifying yield‐limiting factors in wheat is presented.